Portfolio robustness evaluation: a case study in the electricity sector - Lourenço, João Carlos; Soares, João Oliveira; Bana E Costa, Carlos A. (Technological and Economic Development of Economy, 2017)
Managers continually face the task of allocating resources to projects when there is not enough money to fund them all. Portfolio Robustness Evaluation (PROBE) is a multicriteria decision support system developed to help managers to perform that difficult task. This paper presents a PROBE model, developed for an electricity distribution company, to select the best portfolio of projects, subject to budget constraints for different types of projects and various organisational units in multiple time periods. Projects requiring large-scale investments are analysed separately from the small-scale projects. The robustness of the selected portfolio of large-scale projects is analysed in an iterative process where broader uncertainty ranges are considered for the values of the projects, and also when an environmental impact criterion is added to the evaluation model.First published online: 14 Sep 2015